In vitro probiotic properties of Bacillus sp isolated from biofloc reared genetically improved farmed tilapia (Oreochromis niloticus) - MENAGA, M; FELIX, S; CHARULATHA, M (The Indian Journal of Animal Sciences, 2019)
A study was conducted to investigate the probiotic potential of the bacterial species from biofloc reared genetically improved farmed tilapia (GIFT) using in vitro quantitative assays. Based on the morphological, biochemical and 16S rRNA sequencing analysis, isolated bacterial species from GIFT gut were identified as Bacillus infantis, Exiguobacterium profundum, Bacillus subtilis and Bacillus megaterium. The in vitro probiotic properties such as bile salt hydrolase activity, bile tolerance, growth at different bile concentrations, antibiotic susceptibility test, antimicrobial activity, auto aggregation test, bacterial adhesion to hydrocarbons and resistance to gastric acidity were performed. All the isolates showed higher resistance to bile tolerance test and growth of cultures was observed from 0.5 to 8% bile salt concentrations. The distinct zone of hydrolysis was marked in the tested isolates in bile salt hydrolysis activity. Except B. infantis, all the other three isolates were predominantly resistant to the tested antibiotics. Antimicrobial activity against three pathogens, viz. Vibrio parahaemolyticus, Vibrio harveyi and Aeromonas hydrophila was observed in all the isolates. E. profundum and B. subtilis showed improved auto aggregation. Enhanced resistance to bile salt adhesion to hydrocarbon and in vitro gastric acidity (pH 3) was seen in B. megaterium. It is one of such unique studies confirming the probiotic effect of Bacillus sp. isolated mainly from GIFT biofloc culture. B. subtilis and B. megaterium exhibited remarkable in vitro probiotic properties and thus can be recommended as a successful probiotic strain for fish farming.